Development of a Traditional Rice Flour (Suwendal) Incorporated Coating for Chicken Fingers - Subramaniam, T.; Jayawardana, B.C.; Nirosh, L.; Vidanarachchi, J.K. (International Symposium on Agriculture and Environment 2014 University of Ruhuna Sri Lanka, 2014)
Preference for functional meat products are increasing in the meat industry. In the present study, the possibility of replacing wheat in the coating of chicken fingers by traditional rice variety, suwendal was studied. Wheat (100%) flour incorporated coated chicken fingers were considered as the control (C). Wheat flour used in coating was subsequently replaced by three levels (T1-15%, T2-30%, and T3-45%) of suwendal rice flour. Sensory evaluation was carried out to evaluate texture, appearance, taste, oiliness, crunchiness and overall acceptability using ten trained panelists. T2 (30% rice flour) showed the highest values for appearance (4.81), external colour (4.31), oiliness (4.75), crunchiness (4.56) and overall acceptability (4.94). All three treatments showed significantly low. TBARs (Thio Barbituric Acid Reactive Substances) values compared to control during first and third week of storage. Total aerobic plate count of all treatments and control increased throughout the storage period. However, there was no significant difference in total aerobic plate count among treatments. T1 showed the highest value for coating pick up (31.89) compared to other treatments. Furthermore, T1 showed the highest value for cooking yield (129.17) and the lowest value for cooking loss (2.06). Suwendal rice flour can successfully replace the wheat up to 30% in the coating of chicken finger with improved sensory and other quality characteristics.
Keywords: Swendal; Chicken fingers; Coated; Rice flour